CREATION OF ANDROID-BASED MOBILE LEARNING MODULES USING GUIDED INQUIRY MODELS FOR HIGH SCHOOL PHYSICS MATERIALS - Fitriane Salsabila Z; gusnedi G; desnita D; renol afrizon (PILLAR OF PHYSICS EDUCATION, 2022)
The development of technology has an impact on the world of education. The use of Information and Communication Technology (ICT) in the world of Education can help learners in describing something abstract such as using images, videos, animations, charts and others. The Regulation of the Minister of Education that required teachers to be able to use learning media and learning resources relevant to the characteristics of learners and subjects that are mastered to achieve the learning goals as a whole. The solution to this problem is the creation of android-based mobile learning modules using a guided inquiry model for high  school physics materials. The purpose of this research is to produce android-based mobile learning modules using guided inquiry models for valid high  school physics materials. The type of research done is Research and Development (R&D). The model used in this study is a four D model (4D model) developed by Thiagrajan. In this study will be limited to the stage of developing, so that only through 3 stages, namely define, design and develop. The data analysis techniques used are quantitative descriptive statistics and qualitative data analysis. The data obtained from this study comes from validity tests through wide validation. Based on validation results by experts obtained an average value of the total percentage in all aspects of 79,25% and declared very feasible. From this research it can be concluded that android-based mobile learning modules using guided inquiry models have been in accordance with the curriculum used and worth using in schools.